Mathematical Communication Ability of Junior High School Students Across Gender - Handini, Azizahnur; Si’ana, Maulidah; Zawawi, Irwani; Suryanti, Sri (FKIP Universitas Lampung, 2022)
The purpose of this study was to describe students' mathematical communication skills in terms of gender differences in class VII-1 of SMP Negeri 1 Dawarblandong. This type of research is quantitative with a descriptive approach. This research was conducted in the even semester of the 2021/2022 academic year at SMP Negeri 1 Dawarblandong. The subjects in this study were class VII-1 students, as many as 32 students consisting of 26 female students and 6 male students. The data in this study were obtained from tests. The test results are used to determine the mathematical communication skills of male and female students in writing. The results of the research showed that mathematical communication skills of male students are included in the poor category with an average value of 29.17 with poor category and female studentss are included in the fairly good category with an average value of by 43.51.Keywords: mathematical communication ability, junior high school students, gender.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1665-1672